PENGARUH WAKTU TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS YANG DITUMPANGSARIKAN DENGAN TANAMAN KACANG TANAH - Ayu Tuti Lestari; Aris Aksarah Pas; Hasmari Noer (Jurnal Agrotech, 2020)
This study aims to determine the right planting time to obtain optimal sweet corn results in intercropping systems with peanut plants. This research was conducted in the Agricultural Land of Petobo Village, South Palu Village, Palu City, Central Sulawesi for 3 months starting from September to November 2017. The research was carried out using a one-factor Randomized Block Design (RBD), by grouping based on water sources. The treatments that were tried were the intercropping system (TS) planting time, as follows: TS0 = Sweet corn grown together with peanuts; TS1 = Sweet corn planted with 2 WAP peanuts; TS2 = Sweet corn planted with 4 WAP of peanut; TS3 = Sweet corn monoculture. Each treatment consisted of 3 replications so that there were 12 test unit plots. The results showed that the planting time treatment significantly affected the growth and yield of sweet corn on intercropping systems with peanuts. The treatment of planting time together between peanuts and sweet corn gave better growth than other treatments, but the sweet corn monoculture (TS3) treatment gave better results compared to other treatments. Good growth and yield of both plants is recommended at the same time between peanuts and sweet corn in intercropping systems